Chronic lymphocytic leukemia antibodies with a common stereotypic rearrangement recognize nonmuscle myosin heavy chain IIA - Chu, Charles C. (American Society of Hematology, 2008)
Leukemic B lymphocytes of a large group of unrelated chronic lymphocytic leukemia (CLL) patients express an unmutated heavy chain immunoglobulin variable (V) region encoded by IGHV1-69, IGHD3-16, and IGHJ3 with nearly identical heavy and light chain complementarity-determining region 3 sequences. The likelihood that these patients developed CLL clones with identical antibody V regions randomly is highly improbable and suggests selection by a common antigen. Monoclonal antibodies (mAbs) from this stereotypic subset strongly bind cytoplasmic structures in HEp-2 cells. Therefore, HEp-2 cell extracts were immunoprecipitated with recombinant stereotypic subset-specific CLL mAbs, revealing a major protein band at approximately 225 kDa that was identified by mass spectrometry as nonmuscle myosin heavy chain IIA (MYHIIA). Reactivity of the stereotypic mAbs with MYHIIA was confirmed by Western blot and immunofluorescence colocalization with anti-MYHIIA antibody. Treatments that alter MYHIIA amounts and cytoplasmic localization resulted in a corresponding change in binding to these mAbs. The appearance of MYHIIA on the surface of cells undergoing stress or apoptosis suggests that CLL mAb may generally bind molecules exposed as a consequence of these events. Binding of CLL mAb to MYHIIA could promote the development, survival, and expansion of these leukemic cells.